Dual-Toxin-Producing Clostridium botulinum Strain Isolated from a Foodborne Botulism Case in Korea: Genomic and Functional Insights - Eun-Sun Choi; Chi-Hwan Choi; Jun-Ho Jeon; So-Hyeon Kim; Hyun-Ju Song; Hwajung Yi; Gi-eun Rhie; Yoon-Seok Chung (Toxins, 2025)
Clostridium botulinum produces one of the most potent biological toxins and causes botulism, a rare but potentially fatal neuroparalytic disease. In 2014, a foodborne botulism case was reported in Korea, and a strain (CB-2014001) was isolated. Initial characterization identified it as a BoNT/B-producing strain based on mouse bioassay and conventional PCR. However, subsequent genomic analysis revealed the presence of dual BoNT gene clusters, bont/B and bont/F, corresponding to subtypes B5 and F2, respectively. Therefore, we aimed to analyze the genetic characteristics and toxin expression profiles of the isolated strain. The strain showed high sequence identity with Bf-type strains such as CDC 3281 and An436. Functional assays confirmed simultaneous expression of both BoNT/B and /F toxins at 35 °C, and temperature-dependent assays revealed predominant expression of BoNT/F at 30 °C and BoNT/B at 37 °C, indicating that toxin expression is influenced by environmental temperature. These findings highlight the potential for differential pathogenicity based on culture conditions and underscore the importance of developing diagnostic tools capable of detecting multiple bont genes. To our knowledge, this is the first report of a dual-toxin-producing C. botulinum strain associated with foodborne botulism in Korea, providing important insights into botulism diagnosis, treatment strategies, and public health preparedness.